Malay-translated version and content validation of parent goals for shared reading questionnaire - Sen, Shui Ping; Mohd Normani Zakaria,; Affizal Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The interaction between adults and children during shared reading contributes to the conversation and reading in hand and makes the activity interactive. It is, therefore, imperative to understand parents’ goals for shared reading with their children as it will influence their behaviour and, in turn, affect their children’s development of language and literacy skills. In Malaysia, no local psychometric instrument identifying parent goals for shared reading is available. This study aims to translate the English version of the Parent Goals for Shared Reading Questionnaire (PGSRQ) into Malay and validate the translated questionnaire. Four qualified translators carried out the translation processes, and a panel of eight experts subsequently validated the Malay-translated version of PGSRQ. Of 33 items, the validation assessment revealed that 17 items had a content validity ratio (CVR) value of 1.0, while 12 items had a CVR value of 0.8. Only four items had a CVR value lower than 0.78 and were retranslated and modified. The findings of this study can pave the way for more research efforts in the field of shared reading in Malaysia. The questionnaire can also assist a speech therapist in assessing the goals that parents have on shared reading to come up with better designs for shared book reading intervention.